2020
DOI: 10.1186/s40643-020-00328-4
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous enzymatic protein and lipid release from the microalgae Chlamydomonas reinhardtii

Abstract: Advances in biochemical and molecular manipulation have led to increased biomass productivity and oil accumulation in the microalgae C. reinhardtii. However, scalable processes for the recovery of oil and other valuable biomolecules, such as protein, from C. reinhardtii are scarce. The use of aqueous enzymatic extraction, a non-solvent and environmentally friendly bioproduct recovery method, provides an opportunity to design an integrated process for oil and protein fractionation to reduce bioenergy and biopro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…It has been established that nitrogen deprivation induces accumulation of TAGs and starch. TAGs, act as a storage of carbon rich compounds, a resource for future recovery (26). Concurrent to earlier research it has been observed that Chlamydomonas spp.…”
Section: Stress In the Algal Cultures Has Led To An Increase In Accumulation Of Lipidssupporting
confidence: 56%
“…It has been established that nitrogen deprivation induces accumulation of TAGs and starch. TAGs, act as a storage of carbon rich compounds, a resource for future recovery (26). Concurrent to earlier research it has been observed that Chlamydomonas spp.…”
Section: Stress In the Algal Cultures Has Led To An Increase In Accumulation Of Lipidssupporting
confidence: 56%
“…Each plate of cells was resuspended in 10 ml of M-N/5 (minimal minus nitrogen / 5) [ 109 ] and rocked in light at room temperature for 3 hrs. Cells were spun at 2,000 x g for 5 min, then resuspended in 10 ml of autolysin [ 114 ] for 1 hr. Next, cells were spun at 2,000 x g for 5 min and resuspended in 750 μl of cell lysis buffer (20 mM Tris-HCl pH 7.5, 5 mM MgCl 2 (Sigma, 232–094, lot #088J00292), 300 mM NaCl (Fisher Scientific, BP358-212, lot #976181), 5 mM Dithiothreitol (RPI Research Products, D11000-5.0, lot #12936482), 0.1% Triton-X100 (EM Science, TX1566-1, lot #31050) [ 64 ], with 20 μM phenylmethylsulfonyl fluoride (Sigma, P-7626, lot #050M1688) and the Protease Inhibitor Cocktail for plants (Sigma, p9599, lot #086K4075).…”
Section: Methodsmentioning
confidence: 99%
“…Each plate was resuspended in 10 ml of M-N/5 and rocked in light at room temperature for 3 hr. Cells were spun at 2,000 x g for 5 min, resuspended in 10 ml of autolysin [144] for 1 hr. Next cells were spun at 2,000 x g for 5 min and resuspended in 600-750 μl of cell lysis buffer (20 mM Tris–HCl pH 7.5, 5 mM MgCl 2 , 300 mM NaCl, 5 mM Dithiothreitol, 0.1% Triton-X100 [93], with 20 μM phenylmethylsulfonyl fluoride (Sigma, Lot # 050M1688) and the Protease Inhibitor Cocktail for plants (Sigma, p9599, lot #086K4075).…”
Section: Methodsmentioning
confidence: 99%